Infrared‐to‐THz Detection and Spectroscopy with Whispering‐Gallery‐Mode Microresonators. Issue 12 (19th August 2022) - D'Ambrosio, Davide; Capezzuto, Marialuisa; Aiello, Roberto; Delli Santi, Maria Giulia; Sorgi, Alessia; Malara, Pietro; Avino, Saverio; Giorgini, Antonio; Maddaloni, Pasquale; Consolino, Luigi; Vitiello, Miriam Serena; Natale, Paolo De; et al.
Abstract : A novel room‐temperature photodetector based on a silica‐microsphere optical resonator operating from the mid‐infrared to the terahertz spectral region is reported. The sensor relies on a free‐space visible laser whose frequency is locked to the center of a whispering‐gallery mode (WGM). The devised scheme automatically tracks any small change in the microresonator's size and refractive index that occurs upon illumination with radiation absorbed by silica. In this way, direct detection of quantum‐cascade laser beams around 4.3 and 111 μm wavelengths is shown, down to minimum noise‐equivalent power levels of ≈1 pW √Hz −1 with a dynamic range >100 dB. The microsphere resonator is then exploited, for the first time, as a photodetector in absorption spectroscopy of the 12 CO2 fundamental ro‐vibrational band and of very‐weak 13 CH3 OH rotational lines. Abstract : A room‐temperature sensor based on an optical microresonator is demonstrated for detection of mid‐infrared and THz radiation. The sensor relies on a free‐space laser locked to a whispering‐gallery mode to measure its response to absorption in the mid‐ and far‐infrared. Radiation detection down to noise‐equivalent power of 1 pnW √Hz −1 and spectroscopy of vibrational and rotational transitions are shown using quantum‐cascade lasers.